Dual‐Encoded Microbeads through a Host–Guest Structure: Enormous, Flexible, and Accurate Barcodes for Multiplexed Assays. (18th July 2016) - Zhang, Ding Sheng‐zi; Jiang, Yang; Yang, Haiou; Zhu, Youjie; Zhang, Shunjia; Zhu, Ying; Wei, Dan; Lin, Ye; Wang, Pingping; Fu, Qihua; Xu, Hong; Gu, Hongchen
Abstract : Bead‐based suspension arrays have attracted increasing attention because of the fast growing requirements for high‐throughput multiplexed bioassays. Here, novel dual‐encoded microbeads (DEBs) based on a host–guest structure are developed. A strawberry‐like structure composed of thousands of dye‐doped nanoparticles closely packed onto the quantum dot‐encoded microbeads is designed and synthesized. Using this 3D structure, the encoded space is fully developed for multicolor encoding. As a result, a 30‐barcode library with an outstanding encoding capacity is successfully established and easily decoded via flow cytometry. The separation of organic dyes and quantum dots into two building blocks helps circumvent the optical mutual interference commonly observed in most multicolor barcodes, bringing great convenience for next‐step decoding accuracy. As a proof of concept, six typical DEBs are chosen and their feasibility in six‐plexed detection for influenza viruses is evaluated. The results show that DEBs can selectively capture the specific targets, with negligible nonspecific absorption; these results thus demonstrate the strong potential of the DEBs as a robust platform for multiplexed bioassays. Abstract : Dual‐encoded microbeads with a host–guest structure are successfully designed using a controllable, flexible, and accurate encoding strategy. The tailored host–guest structure improves the encoding capacity of the barcodes and effectively overcomes the optical mutual interference. The effectiveness of the barcodes as a robust platform for multiplexed bioassays is demonstrated.